Penerapan Jaringan Saraf Tiruan Dalam Memprediksi Gizi Balita Pada Puskesmas Siantar Utara Kota Pematangsiantar - Daniel Arbanus Simbolon; Dedy Hartama; Fitri Anggraini (LPPM STIKOM Tunas Bangsa, 2019)
The North Siantar Health Center's Puskesmas is a health sector engaged in public health sciences, at the Office of the North Siantar Sub-District of Pematangsiantar City conducted research with the Nutritional research variables under five months of age. attacked by various diseases ranging from external diseases and internal diseases. Artificial Neural Network is a method of grouping and separating data whose working principle is the same as Human Neural Networks, this Science processes systems and structures so that they become information.